Faculty awareness, use and attitudes towards scholarly open access: A Pakistani perspective. (September 2019) - Sheikh, Arslan
Open access is a new scholarly publishing model that aims to provide free access to scholarly information to all members of society. This study analyzes the awareness, use and attitudes of Pakistani faculty members towards scholarly open access. A structured questionnaire was designed to collect data from the respondents by using an online survey tool, Google Forms. The population of the study was the faculty members of 21 universities and higher education institutions located in Islamabad. A sample of 3000 faculty members were invited, through email, to participate in the study; of which 616 completed the survey, with a response ratio of 20.53%. Descriptive statistics and (SPSS) version 21.0 were used for data analysis. The findings of the study reveal that, although majority of the Pakistani faculty members (71.5%) were aware of the scholarly open access before this survey, their awareness level about open access-related resources and initiatives was very low. The Pakistani faculty members used open access venues more frequently to access scholarly contents rather than to publish their own research works. A lack of awareness to publish in open access venues, and publication fees of open access journals were the key challenges faced by the Pakistani faculty members. The attitudes of faculty members towards open access were very positive in all contexts. Large readership, impact factor, free access to readers and no publication fee were the key motivational factors for the faculty members to publish in open access journals.